Pengenalan Sis-Log in Apps sebagai E-Commerce untuk Kelompok Usaha Tani Karawang pada Masa Pandemi Covid-19 - Wahyudin Wahyudin; Dene Herwanto; Wahyudin Fitriyana; Billy Nugraha (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The problem that is happening in the field in the form of agricultural products is information that is often found today. From these problems linking farmers and distributors, of course, has an impact on long shipping flow. In addition, coupled with the presence of Pandemi Covid-19 which caused agricultural distribution to be hampered. So the purpose of this service designs applications that are the needs of farmers, so that vegetables can be directly to consumers. Sis-Log in Apps (Agricultural Logistics System Application) is an application designed by researchers and can be used for the needs of farmers and consumers. The method used in this service is a field method. The results in this service are in the form of sis-log design in apps. Applications are useful to facilitate the process of buying and selling directly between farmers and consumers. Without going through other intermediaries that make the shipping network long. Then the quality of the freshness of vegetables is maintained and directly to the hands of consumers. In addition, this application uses technology that is looking for the closest distance between farmers and consumers. So this makes the effectiveness and efficiency of vegetable delivery.